A study of burnout and stressor-related factors among caretaker of children with chronic neurological illness - Abdullah, Siti Ai'syah (2020)
Objective: Caring for children with neurological condition is challenging. This study aimed to determine the prevalence of burnout and its associated factors in caretakers of children with chronic neurological illness. Methods:Thiscross-sectional study involved 18 years or older caretakers of children with neurological illness for more than 3 months duration. They were recruited from Paediatric Neurology outpatient clinics over a period of 3 months from July to October 2019 at a general hospital inthe state of Kelantan, Malaysia. Each caretaker was given a set of questionnaires, that included General Stressor Questionnaire (GSQ) which was translated into Malay version ‘SoalSelidikUmum (SSU)’, Copenhagen Burnout Inventory-Malay version (CBI-M) and Demographic Information Form. Results: Two hundred and forty caretakers of children with chronic neurological illness participated in the study. The mean age of caretaker was 38.12 years old (SD = 7.74). Majority of them were female (82.1%), Malay (94.6%) and Muslim (95.8%). Mean age of children with chronic neurological illness was 7.19 years old (SD = 4.21), and most of them were male (60.8%) and had the illness for more than 5 years (38.3%). Overall only 20 caretakers had mean score of 50 or higher in all component in CBI-M, making the prevalence of total burnout among the caretakers of 8.3% (95% CI = 5.2%, 12.6%). The prevalence of burnout differs for each domain. Personal burnout involved 78 caretakers (32.5%, 95% CI = 26.6%, 38.8%), 42 caretakers with clientrelated burnout (17.5%, 95% CI = 12.9%, 22.9%) and 11 caretakers had work-related burnout (4.6%, 95% CI = 2.3%, 8.1%). The highest prevalence of personal burnout was among caretakers of children with genetic illness (60.0%, 95% CI = 26.2%, 87.8%), followed by cerebral palsy (43.5%, 95% CI = 31.0%, 56.7%) and autism (37.5%, 95% CI = 18.8%, 59.4%). The highest prevalence of total burnout was among caretaker of children with genetic illness (30.0%, 95% CI = 6.7%, 65.2%), followed by intellectual disability (20.0%, 95% CI = 0.5%, 71.6%) and autism (16.7%, 95% CI = 4.7%, 37.4%). Most common stressors were performance pressure, work-family conflict and poor job prospect. Multiple logistic regression analysis showed that family stressor, types of children’s neurological illness and number of household occupants were associated with personal burnout, client-related burnout and total burnout in their caretakers. Conclusions: Prevalence of total burnout among the caretakers were low, but personal burnout was prominent. Caretakers of children with genetic disorder, cerebral palsy and autism had higher prevalence of burnout compared to other chronic neurological illness.